HUBUNGAN TINGKAT AKTIVITAS FISIK DENGAN INDEKS MASSA TUBUH PADA KELAS IV – VI FASE B DAN C DI SDN MOJOROTO 2 KOTA KEDIRI - Nabilla Puri Damaisari; Budiman Agung Pratama; Puspodari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by preliminary observations at SDN Mojoroto 2, where variations in Body Mass Index (BMI) among school-aged children indicated differences in nutritional status, potentially linked to physical activity levels. However, the relationship between physical activity levels and BMI requires further investigation to clarify the connection between these two variables. This study employed a quantitative research approach, with the subjects comprising all students in grades 4, 5, and 6 at SDN Mojoroto 2. The instruments used included the Physical Activity Questionnaire for Children (PAQ-C), BMI measurements, and BMI classification guidelines for children (based on WHO/Ministry of Health standards). The study concluded that: (1) Hypothesis testing revealed a significant relationship between physical activity and BMI among students in grades 4–6 at SDN Mojoroto 2 (significance value of 0.000); and (2) The strength of the relationship between physical activity levels and BMI was 15.6%. Based on these findings, it is recommended that: (1) Schools and teachers enhance guidance and instruction tailored to student characteristics to optimize outcomes; and (2) Future research incorporate additional variables that may influence the relationship between physical activity and BMI.